Ketahanan Pangan Bagi Anak di Masa Pandemi Covid-19: Sebuah Hak Fundamental (Perbandingan Indonesia-Malaysia): Food Security for Children during the Covid-19 Pandemic: A Fundamental Right (Comparison of Indonesia-Malaysia) - Rodiyah, Rodiyah; Utari, Indah Sri; Arifin, Ridwan; Waspiah, Waspiah; Damayanti, Ratih (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Food insecurity among children poses a significant threat to the healthy development of children around the world such as stunted growth, poor cognitive development, stress, illnesses, and many other negative repercussions which further leads to socio-emotional and behavioural consequences. A new study released by UNICEF reveals higher levels of poverty and malnutrition among children living in low-cost housing in Kuala Lumpur, compared to the national average, as well as in some cities in Indonesia. If children from the urban poor suffer from food insecurity, what more the children living in the rural areas who may suffer the same. Which is why Sen’s Entitlement theory attributes food insecurity to poverty which prevents affordability and accessibility to food. Political and other tangible interventions should be undertaken to address food insecurity not only to promote healthy development of children in Indonesia and Malaysia but also to assure sustainability of food security as a precautionary approach. A starting point to ensure food security among children should be the school where children spend most of their time in a day.